2018
DOI: 10.1007/s13178-018-0331-3
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Same-Sex Marriage and Parenting, Ideologies, and Social Contacts: the Mediation Role of Sexual Prejudice Moderated by Gender

Abstract: Recognition of same-sex marriage and parenting has increased in the last two decades but remains a controversial issue in which public opinion plays a role, as it can influence political leaders but also determine the immediate environment of same-sex families. The literature highlights the effect of religiosity, political orientation, beliefs about etiology of homosexuality, and social contacts with gay men and lesbians on attitudes toward same-sex marriage and parenting (ASSMP). The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 52 publications
3
17
0
Order By: Relevance
“…Our results confirmed H1b and H3, because heterosexual males had higher mean learned etiology scores than heterosexual females or LGs and the effects of learned etiology on IO (H3a) and NO (H3b) to same-sex parenting were significant in the overall sample. This is generally supportive of previous studies' results, which found that people who believe homosexuality is learned are more strongly opposed to samesex parenting than those who argue on behalf of genetic etiology (Costa et al, 2018;Frias-Navarro et al, 2018;Vecho et al, 2019). Notably, the paired samples t-test revealed LGs had higher means for genetic etiology, and heterosexual participants had higher means for learned etiology, which demonstrated the sexual orientation divide between the respondents in their beliefs about homosexuality etiology.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our results confirmed H1b and H3, because heterosexual males had higher mean learned etiology scores than heterosexual females or LGs and the effects of learned etiology on IO (H3a) and NO (H3b) to same-sex parenting were significant in the overall sample. This is generally supportive of previous studies' results, which found that people who believe homosexuality is learned are more strongly opposed to samesex parenting than those who argue on behalf of genetic etiology (Costa et al, 2018;Frias-Navarro et al, 2018;Vecho et al, 2019). Notably, the paired samples t-test revealed LGs had higher means for genetic etiology, and heterosexual participants had higher means for learned etiology, which demonstrated the sexual orientation divide between the respondents in their beliefs about homosexuality etiology.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies on the relationship between beliefs about the etiology of homosexuality and children in same-sex families revealed that people who believed that homosexuality is learned have higher scores on the IO and the NO subscales than those who believed homosexuality was genetic (Frias-Navarro et al, 2018;Vecho, Gross, Gratton, D'Amore, & Green, 2019). However, one study only identified a difference in the IO subscale (Frias-Navarro et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This may be explained by the socialization of young generations who have been more exposed to diverse models of sex, love, family, and culture than older generations who were educated with traditional models of marriage and parenting (Hegarty, 2018). Furthermore, heterosexual men often have more negative attitudes toward SSM and LGP compared to women, presumably because of their acculturation to more rigid sexual and gender roles and expectations based on gender role traditionalism, heterosexism, and masculine ideals regarding virility, strength, and male dominance (Costa et al, 2017;Vecho et al, 2018). Men's hostile attitudes are also stronger against gay males than lesbian couples; these are primarily based on heterosexism and traditional gender role beliefs (Costa et al, 2017;Salvati, Ioverno, Giacomantonio, & Baiocco, 2016).…”
Section: Attitudes Toward Lg People Ssm and Lgpmentioning
confidence: 99%
“…Among the psychological predictors of attitudes toward LG people, SSM, and LGP, intergroup contact with LG people (a frequency of interaction with lesbian and gay people) has been found to be one of the most relevant Vecho et al, 2018). Intergroup contact tends to decrease prejudice, especially if this contact entails a positive interaction between majority and minority group members (Pettigrew & Tropp, 2008;Vezzali & Stathi, 2017).…”
Section: Attitudes Toward Lg People Ssm and Lgpmentioning
confidence: 99%